2013
DOI: 10.1088/1748-9326/8/4/045027
|View full text |Cite
|
Sign up to set email alerts
|

Subjective risk assessment for planning conservation projects

Abstract: Conservation projects occur under many types of uncertainty. Where this uncertainty can affect achievement of a project's objectives, there is risk. Understanding risks to project success should influence a range of strategic and tactical decisions in conservation, and yet, formal risk assessment rarely features in the guidance or practice of conservation planning. We describe how subjective risk analysis tools can be framed to facilitate the rapid identification and assessment of risks to conservation project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…We asked each respondent to represent the experiences of their organisation. Our sampling approach is consistent with other research employing expert elicitation, network and participatory approaches (e.g., Cohen et al 2012;Game et al 2013) and it aligns with methodological approaches in leadership studies (e.g., Mailhot et al 2016) The face-to-face expert interview involved a participatory network mapping activity to map leadership influences on the respondents' organizations. First we asked respondents to identify "Who and what provides leadership in the work that your organisation does (e.g., activities on the ground, policies your organisation develops, research your organisation undertakes, etc.)…”
Section: Data Collectionmentioning
confidence: 64%
“…We asked each respondent to represent the experiences of their organisation. Our sampling approach is consistent with other research employing expert elicitation, network and participatory approaches (e.g., Cohen et al 2012;Game et al 2013) and it aligns with methodological approaches in leadership studies (e.g., Mailhot et al 2016) The face-to-face expert interview involved a participatory network mapping activity to map leadership influences on the respondents' organizations. First we asked respondents to identify "Who and what provides leadership in the work that your organisation does (e.g., activities on the ground, policies your organisation develops, research your organisation undertakes, etc.)…”
Section: Data Collectionmentioning
confidence: 64%
“…Risks can never be fully eliminated but it can be managed effectively to minimize and mitigate the impacts on expected outcomes of the project [14]. "The aim of conservation planning is not to reduce risk per se but to maximize performance of the chosen strategies" [12]. Risk assessment will prioritize which risks need to be managed in conservation project.…”
Section: Analyses and Discussionmentioning
confidence: 99%
“…Conservation work also involved risks where Umi Kalsum et al [2] believe that risks in conservation project are actually much higher than new building project. Game, Fitzsimons, Lipsett-Moore & McDonald-Madden [12] mention that "understanding risks to project success should influence a range of strategic and tactical decisions in conservation, and yet, formal risk assessment rarely features in the guidance or practice of conservation planning". This is supported by Umi Kalsum et al [2] when they also found that risk management in conservation projects had been poorly practiced and applied nowadays.…”
Section: Categories Of Risks In Conservation Projectmentioning
confidence: 99%
“…These include the tropical savannas of northern Australia (e.g. Fitzsimons and Looker 2012;Game et al 2013), Gondwana Link and the Great Western Woodlands (e.g. Bradby 2013;Bradby et al 2014;Fitzsimons et al 2014), temperate bays and estuaries of southern Australia (Fitzsimons et al 2015) and the aridlands of central Australia.…”
Section: Building a Land Management Programmentioning
confidence: 99%